Surface modified hydroxyapatites with various functionalized nanostructures: Computational studies of the vacancies in HAp. (12th March 2017) - Bystrov, V. S.; Paramonova, E. V.; Dekhtyar, Yu. D.; Bystrova, A. V.; Pullar, R. C.; Kopyl, S.; Tobaldi, D. M.; Piccirillo, C.; Avakyan, L. A.; Coutinho, J.
ABSTRACT: Hydroxyapatite (HAp) has structural features that define its basic physical properties, which have an important role at the surface, and it is one of the most used materials in bone implants. In this work, we present a density functional modeling (DFT) study of HAp both as bulk and with special HAp models with various defects, especially oxygen vacancies in HAp surface layers, which can also determine photocatalytic properties, confirmed experimentally. The first-principles calculations of bulk and modified HAp were carried out using local basis (AIMPRO) and plane-wave (VASP) codes. Data obtained are analyzed using both approaches, and compared.